Role of Ethical Leadership in Reducing Workplace Bullying in Multinational Corporations in China - Yan, Chen (Human Resource and Leadership Journal, 2025)
Purpose: The purpose of this article was to analyze role of ethical leadership in reducing workplace bullying in multinational corporations in China. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: ​ Ethical leadership in Chinese multinational corporations reduces workplace bullying by promoting respect, fairness, and accountability. Leaders who model ethical behavior discourage abuse of power and create a safe, supportive work culture. This approach fosters trust, empowers employees to report mistreatment, and lowers bullying incidents. Overall, ethical leadership plays a key role in preventing toxic behaviors at work. Unique Contribution to Theory, Practice and Policy: Social learning theory, ethical climate theory & transformational leadership theory may be used to anchor future studies on role of ethical leadership in reducing workplace bullying in multinational corporations in China. Organizations should establish safe and confidential reporting channels that empower employees and bystanders to report bullying without fear of retaliation, supported by leaders who actively intervene and model ethical behavior. On the policy front, multinational corporations should develop global governance frameworks that mandate ethical leadership standards and ensure consistent anti-bullying measures across all subsidiaries worldwide.